To find the point of intersection, we can solve the two equations simultaneously.
From the second equation, we know that y = x + 3. We can substitute this into the first equation:
-x - (x + 3) = 1
-x - x - 3 = 1
-2x - 3 = 1
-2x = 4
x = -2
Now that we have found the x-coordinate of the point of intersection, we can substitute this back into the second equation to find the y-coordinate:
y = -2 + 3
y = 1
Therefore, the point of intersection is (-2, 1), which is option B.
Consider the following equations:
−x − y = 1
y = x + 3
If the two equations are graphed, at what point do the lines representing the two equations intersect? (4 points)
A. (−1, 2)
B. (−2, 1)
C.(1, −2)
D.(2, −1)
1 answer